Sustainability in Buildings: New Trends in the Management of Construction and Demolition Waste Volume I - Morón Fernández, Carlos; Ferrández Vega, Daniel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Topic, "Sustainability in Buildings: New trends in the management of construction and demolition waste", collected works related to the use of new sustainable building materials, new trends in the recycling of materials for their application in construction, and the application of new techniques and measurement processes that favour the development of sustainable construction. This printed work contains some of the most cutting-edge research carried out by leading international researchers in the field of building engineering. In this way, the work complements the existing literature on construction and demolition waste management from a multidisciplinary perspective, which encourages the exchange of ideas and points of view.